PENINGKATAN KUALITAS PEMBELAJARAN TEMATIK MELALUI MODEL PEMBELAJARAN AKTIF TIPE INDEX CARD MATCH - Khoirul Huda, Mei Fita Asri Untari, (MALIH PEDDAS, 2013)
Stage of development of the child in accordance with the characteristics of how children learn, the learning process is the most appropriate thematic learning. Thematic is tepadu learning by using themes to associate some subjects so as to provide a meaningful experience to the students. Based on initial observations in class II Banyutowo Kendal SDN 2 shows the results of student learning is not maximized, because the teachers have not been using a variety of methods, inadequate instructional media, student activities passive and apathetic. Achievement of classical completeness for the Civics subjects and 37.5% for subjects Indonesian namely 45.8%. This research is a classroom action research (CAR). In this PTK is the subject of the study is the second grade students of SDN Banyutowo Kendal, amounting to 24 students. The study was planned in the second semester of academic year 2012/2013. By using about as much as 20 points to the data analysis used descriptive analysis includes determining the completeness of individual and classical. Results of this study showed improvement of teacher skills, student activities, and student learning outcomes in thematic learning through active learning model type Index Card Match. Average student activity increased less than 47% category (first cycle), a good 75% category (cycle II). The average teachers skills increased from 47% category of very less (first cycle), a good 72% category (cycle II). Average student learning outcomes increased from an average value of 58.75 with classical completeness 37.5% lower category (first cycle), has increased the average value is 78.75 with classical completeness of 83.3% is very high category (cycle II). Based on the results of this study concluded that the active learning model Index Card Match type proven to improve the quality of thematic learning indicated on improving the skills of teachers, student activities and student learning outcomes. Suggestions should be submitted to teachers seeking to improve the quality of learning in the classroom by applying active learning model Index Card Match type which can improve the skills of teachers, student activities, and student learning outcomes.